2018
DOI: 10.1016/j.omtn.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-300 Regulates the Ubiquitination of PTEN through the CRL4BDCAF13 E3 Ligase in Osteosarcoma Cells

Abstract: Cullins, critical members of the cullin-RING ubiquitin ligases (CRLs), are often aberrantly expressed in different cancers. However, the underlying mechanisms regarding aberrant expression of these cullins and the specific substrates of CRLs in different cancers are mostly unknown. Here, we demonstrate that overexpressed CUL4B in human osteosarcoma cells forms an E3 complex with DNA damage binding protein 1 (DDB1) and DDB1- and CUL4-associated factor 13 (DCAF13). In vitro and in vivo analyses indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 55 publications
6
74
0
1
Order By: Relevance
“…34 Moreover, recent studies have revealed that protein ubiquitination and protein binding in osteosarcoma provide a new avenue for osteosarcoma therapy. [35][36][37][38][39][40] In other words, all these theories are in agreement with our results. GO enrichment analysis revealed that changes in the hub genes were mainly enriched in nucleolus, protein ubiquitination, and protein binding, while enriched in RNA transport and the spliceosome in the KEGG pathway.…”
Section: Discussionsupporting
confidence: 93%
“…34 Moreover, recent studies have revealed that protein ubiquitination and protein binding in osteosarcoma provide a new avenue for osteosarcoma therapy. [35][36][37][38][39][40] In other words, all these theories are in agreement with our results. GO enrichment analysis revealed that changes in the hub genes were mainly enriched in nucleolus, protein ubiquitination, and protein binding, while enriched in RNA transport and the spliceosome in the KEGG pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Cullins can form E3 ligases and participate in the tumorigenesis of many cancer types . To test whether cullin family members are involved in the tumorigenesis of CAC, we isolated RNAs from cancerous tissues and their adjacent non‐tumour tissues in 48 CAC patients and examined the mRNA levels of cullins.…”
Section: Resultsmentioning
confidence: 99%
“…The human genome encodes two E1s, ∼40 E2s and more than 600 E3s . Of these E3 ligases, Cullin‐RING ligases (CRLs), the largest subfamily that is conservatively formed by cullins (CUL1, ‐2, ‐3, ‐4A, ‐4B, ‐5 and ‐7), RBX1, DDB1 and DDB1‐ and CUL4‐associated factors (DCAFs), ubiquitinate ∼20% of cellular proteins . Dysregulation of cullin proteins, especially CUL4A and CUL4B, in different cancer types including breast cancer , hepatocellular carcinoma and osteosarcoma is widely known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work revealed that miR-323a-3p, miR-433 and miR-409 transcribed from this cluster acted as tumor suppressors [16][17][18]. miR-300, belonging to the DLK1-DIO3 miRNA cluster, was previously reported to be associated with human osteosarcoma, pancreatic cancer, non-small cell lung cancer, glioblastoma, and oral squamous cell carcinoma [20][21][22][23][24]. However, to the best of our knowledge, the role miR-300 in BCa and its mechanism remains unresolved.…”
Section: Introductionmentioning
confidence: 99%